1986
DOI: 10.1136/hrt.55.6.543
|View full text |Cite
|
Sign up to set email alerts
|

In vivo production of prostacyclin and thromboxane in patients with acute myocardial infarction.

Abstract: The in vivo production of prostacyclin and thromboxane was monitored by measuring their major urinary metabolites 2,3-dinor-thromboxane B2 and 2,3-dinor-6-keto-prostaglandin F1 alpha in ten patients with acute myocardial infarction, five on standard treatment and five receiving prostacyclin infusion. During acute myocardial infarction excretion of 2,3-dinor-thromboxane B2 and 2,3-dinor-6-keto-prostaglandin F1 alpha, measured by a gas chromatography-mass spectrometry method with deuterated internal standards, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 15 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…One study [41] has also shown that these large platelets are denser. In addition, patients with acute MI show a shortening of the bleeding time when compared to controls [27,44,45], an increase in thromboxane B2 excretion [46,47,48] and an increase in the bleeding time sensitivity to aspirin ( Fig. 2) [45], suggesting that the platelets of these patients may have an elevated activity of the cyclo-oxygenase pathway.…”
Section: Hyperfunctional Platelets In Coronary Artery Thrombosis and mentioning
confidence: 99%
“…One study [41] has also shown that these large platelets are denser. In addition, patients with acute MI show a shortening of the bleeding time when compared to controls [27,44,45], an increase in thromboxane B2 excretion [46,47,48] and an increase in the bleeding time sensitivity to aspirin ( Fig. 2) [45], suggesting that the platelets of these patients may have an elevated activity of the cyclo-oxygenase pathway.…”
Section: Hyperfunctional Platelets In Coronary Artery Thrombosis and mentioning
confidence: 99%
“…In the canine model of coronary stenosis associated with endothelial injury, Golino et al (18) have described that one of the TXA2 receptor antagonists, SQ29548, abolishes cyclic flow variations and results in an increase in the left anterior descending artery cross-sectional area. It is also known that TXA2 formation increases in patients with acute MI (19). Therefore, the role of TXA2 in our MI model is clear and seems similar to the canine model and patients with acute MI.…”
Section: Discussionmentioning
confidence: 63%
“…923 - 27 Thus, activation of TXA 2 formation, largely from platelets, is a consistent finding soon after the occurrence of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 92%